2022
DOI: 10.1016/j.ajic.2021.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Non-ventilator associated hospital acquired pneumonia incidence and health outcomes among U.S. veterans from 2016-2020

Abstract: Among 1,635,711 Veteran acute care admissions (FY2016-2020), the risk of non-ventilator associated hospital acquired pneumonia (NV-HAP) was 1.26 cases per 1,000 hospitalized days and decreased linearly over time with an uptick in cases in the last year coinciding with the onset of the covid-19 pandemic. Veterans who develop NV-HAP experience remarkably higher 30-day and 1-year mortality, longer length of stay, and higher rates of inpatient sepsis. Monitoring and prevention measures may substantially reduce neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 7 publications
3
20
2
Order By: Relevance
“…Contrary to what has been described in other studies [19], we found that incidence of HAP increased in subjects without COPD over time, both in those with (NV)-HAP and those with VAP. However, in subjects with COPD, incidence figures remain stable throughout the study period.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to what has been described in other studies [19], we found that incidence of HAP increased in subjects without COPD over time, both in those with (NV)-HAP and those with VAP. However, in subjects with COPD, incidence figures remain stable throughout the study period.…”
Section: Discussioncontrasting
confidence: 99%
“…In line with our results, previous studies have shown that COPD is a risk factor for HAP [2]. It has also been described that patient who develop (NV)-HAP have more comorbidities including COPD [5,19]. The greater susceptibility of COPD patients to the development of pneumonia may be due to their clinical characteristics, such as mucus production in patients with chronic bronchitis and the potential presence of pathogenic bacteria in the airways, which may increase during exacerbations and be associated with increased inflammation and the host immune response [20].…”
Section: Discussionsupporting
confidence: 92%
“…Our database showed that the frequency of HAP increased significantly from 2016 to 2019 irrespective of T2DM status. This trend is not consistent with data from other population-based studies [ 3 , 26 ], which is probably because of methodological differences in the calculation of HAP rates.…”
Section: Discussioncontrasting
confidence: 92%
“…Its incidence increases over time and varies considerably with age and comorbidities [ 1 ]. HAP more commonly occurs in non-ventilated patients [ 2 , 3 ]. In their analysis of the US National Inpatient Sample dataset, Giuliano et al [ 4 ] found that non-ventilator hospital-acquired pneumonia (NV-HAP) led to an increase in costs, length of stay, and mortality in hospitalized patients.…”
Section: Introductionmentioning
confidence: 99%
“…123,124 NV-HAP is associated with a significantly longer length of stay, high 30day readmission rates, a greater need for intensive care management and long-term care following discharge, increased direct care costs, and perhaps most importantly, it is a frequent source of sepsis. [124][125][126] As noted in a September 2021 Joint Commission Safety Briefing, NV-HAP is a substantial threat to patient safety and a large driver of health care cost, yet it is not formally tracked or reported to the National Database of Nursing Quality Indicators or the CDC NHSN nor does it impact the Centers for Medicare and Medicaid Services payfor-reporting or performance programs. 127 NV-HAP surveillance is not currently standardized, and risk stratification is not reliable, therefore, consideration should be given to application of universal prevention guidelines throughout every patient's hospital or longterm care stay.…”
Section: Hai Surveillance and Prevention: Nonventilator Hospital Acqu...mentioning
confidence: 99%